History Culture And Archaeological Studies (Set Of 3 Vols): Recent Trends Commemoration Volume To Prof. M.l.k. Murty - Reddy Pedarpu Chenna (B.r. Publishing Corporation)
Prof. Pedarapu Chenna Reddy Born in 1959 zangalapalli village in Ananthapuram, got his Post Graduate Degree in History from S.K. University, Anantapur in 1984. Ph.D in History in 1988 from S.V.University. He took Master of Tourism Management Degree from Madurai Kamaraj University in 2007. His book Guilds in Medieval Andhra Desha was widely acclaimed by the academicians and students alike. Dr. Reddy has to his credit more than 35 Books and 120 research papers on various aspects of archaeology, ancient, medieval and modern History published in National and International Journals.. He is life member in more than 54 various Historical and Cultural organizations. He is member of Board of studies in many universities and Government organizations and he was expert member in Promotion and Strengthening of local and regional Museums, a National Body of Ministry of Culture, Govt. of India. He was elected as the Vice President, South Indian History Congress, during 2001-2003, 2006-2008 and 2015-2017. He is an active social worker and educationist. He was the Founder Secretary and was instrumental in establishing in Government Degree College, Dr. Ambedkar Open University Study Centre and Founder Director of 21 st Century Gurukulam in the Srisailam Tribal Area for the poor, dalit and tribal people. He served as Secretary, College Planning and Development Council, Government Degree College, Srisailam for 16 years (1993-2008), President, Lions$1 (BClub International, 324D3, Srisailam, 2004-2005 , Secretary, Indian Red cross Society,Srisailam 2004-2006. He served as Joint Secretary, Andhra Pradesh History Congress and South Indian History Congress. He received several felicitations and awards such as Global Telugus Glory Award (1995), Intach Heritage Award(2010) & (2011), Eminent Educationist Award (2008); Puratatva Vibhushana Award (2009): Dr. Y S Rajasekhar Reddy Memorial Award (2010); Rayalaseema Ratna Award (2011); Mother Teresa Award (2011); Global Peace Award (2011); 35th CITD Ns